Comment: The Re-Politicization of the Fed - Mann, Maurice (Journal of Financial and Quantitative Analysis, 1974)
Edward Kane alleges that the Federal Reserve System recently has taken a turn for the worse, with respect to monetary policy, in that Chairman Burns has re-politicized the System beyond prudent bounds. It is interesting to note that Kane changed the title of his paper from “The Politicization of the Fed” in his first draft (and before he had heard my comments at the meeting) to “The Re-Politicization of the Fed” in his second draft (after he had heard my comments). In my view, Kane's latest title is closer to the truth–though still somewhat misleading–in that, over time, the Fed has necessarily factored political and social considerations into the formulation of economic and monetary policy. But so what, and what else is new? The examples cited by Kane to “document” his case can best be characterized as allegations that illustrate a certain behavioral pattern over time, but these examples fail to support his case that–because of the repoliticization of the Fed–recent monetary policy has been at times counterproductive to the public interest. Perhaps a more legitimate conclusion that Kane could have reached from his observations of public policy in recent years is that the appointment of Dr. Burns as Chairman of the Committee on Interest and Dividends tended to formalize the quasipolitical nature of the position of the Chairman of the Federal Reserve Board.